Using an unusual resource: dung beetles attracted to millipedes (Diplopoda: Spirobolida) - Sánchez-Hernández, Gibrán (2019)
Between 2017 and 2018, samplings out for four months in a tropical evergreen forest fragment from a natural protected area of Chiapas, Mexico, were carried. Pitfall traps were installed along a path of about 500 m. The traps were baited with freshly killed individuals of Messicobolus magnificus, an abundant millipede during the rainy season in the reserve. 108 individuals of four beetles’ species were captured: Canthon vazquezae (92), Deltochilum pseudoparile (13), Coprophanaeus corythus (2) and Ateuchus rodriguezi (1). Only D. pseudoparile has been previously collected with carcasses from other millipede species. The use of this resource type is possibly an alternative source that reduces interspecific competition among the Scarabaeinae for other ephemeral resources.